A comparative study of bilateral ilioinguinal and iliohypogastric nerve block for postoperative analgesia in lower segment cesarean section - Poudel, Anjali; Dutta, Prashant Kumar (Journal of Society of Anesthesiologists of Nepal, 2018)
Background: Modern techniques incorporate regional anesthesia in pain management and it is the best and safest technique. It avoids the side effects that remain with the traditional use of opioids. Ilioinguinal and iliohypogastric nerve block can provide a satisfactory postoperative analgesia in parturients with pfannenstiel incision thereby reducing postoperative opioid consumption. Objective: To compare opioid consumption and pain relief postoperatively with ilioinguinal and iliohypogastric nerve block in patients undergoing lower segment cesarean section. Methods: It is a hospital based comparative study done in Nepalgunj Medical College Teaching Hospital, Kohalpur, Banke in a period of one year. Total of sixty patients, thirty in each were randomly allocated into the two groups. Group B received bilateral ilioinguinal and iliohypogastric nerve block by landmark technique with 20ml of 0.5% bupivacaine; 10ml in each side. Group NS received ilioinguinal and iliohypogastric nerve block with 20ml of 0.9% normal saline. In postoperative period blood pressure, pulse, oxygen saturation, numerical rating scale score at different allocated duration, total dose of tramadol consumption and time to first dose of tramadol were recorded. Results: The total postoperative tramadol consumption in the first 24hr postoperatively was significantly less in group B (125 ± 34.11mg) than in group NS (205 ±37.93mg). The mean effective duration of analgesia measured from the time of onset of spinal blockade to the time of request for tramadol was 264 ±78.27 minutes in group B and 178.17±30.61minutes in group NS, which was statistically significant and also numerical rating scale scores were low at all points postoperatively in group B. Conclusion: Bilateral ilioinguinal and iliohypogastric nerve block significantly lowers the consumption of tramadol and also provides adequate postoperative pain relief. Journal of Society of Anesthesiologists of Nepal Vol. 4, No. 2, 2017, page: 81-86